Long-Range Proton Conduction across Free-Standing Serum Albumin Mats - Paul Meredith (Advanced Materials, 2016)
Proton conductors are commonly used in a variety of applications, mainly in fuel-cells and batteries. While all of the proton-conducting materials in these applications are inorganic or organic, there is great scientific effort to expand the breadth of proton-conducting materials to biologically-derived materials. Here, we explore proton conductivity across free-standing mats composed of bovine serum albumin, one of the cheapest commercially available proteins. We examine both photo-induced proton transfer and long-range (millimetre length-scale) proton conductivity along the mat. Our results, together with temperature dependent and isotope effect measurements, demonstrate that oxo-amino-acids of the protein have a major role in their ability to translocate protons. We further discuss our results in the context of the ‘over-the-barrier’ proton hopping mechanism, which distinguishes them from the common pro-ton hopping mechanism across water. The use of cheap proton-conducting free-standing protein mats opens new possibilities for various types of applications including those in the emergent field of bioelectronics where biocompatible materials capable of transducing ion and electron currents are required.